2009
DOI: 10.1002/cne.22237
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular glutamate transporter 3‐expressing nonserotonergic projection neurons constitute a subregion in the rat midbrain raphe nuclei

Abstract: We previously reported that about 80% of vesicular glutamate transporter 3 (VGLUT3)-positive cells displayed immunoreactivity for serotonin, but the others were negative in the rat midbrain raphe nuclei, such as the dorsal (DR) and median raphe nuclei (MnR). In the present study, to investigate the precise distribution of VGLUT3-expressing nonserotonergic neurons in the DR and MnR, we performed double fluorescence in situ hybridization for VGLUT3 and tryptophan hydroxylase 2 (TPH2). According to the distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
212
1
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(259 citation statements)
references
References 88 publications
21
212
1
14
Order By: Relevance
“…There is a weak Galr2 mRNA signal in the midline area/cells of the DR (32,34), which is supported by the data of others (23,63) as well as present qPCR data, and speculatively expressed in a population of 5-HT neurons. These GALR2 + neurons could express VGLUT3 + (90-93), although there are also VGLUT3 + , 5-HT − neurons in that area (91). Eberwine and Bartfai (94) and Bartfai et al (95) have reported that a single warm-sensitive neuron in the hypothalamus may contain several hundred receptor transcripts, however.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a weak Galr2 mRNA signal in the midline area/cells of the DR (32,34), which is supported by the data of others (23,63) as well as present qPCR data, and speculatively expressed in a population of 5-HT neurons. These GALR2 + neurons could express VGLUT3 + (90-93), although there are also VGLUT3 + , 5-HT − neurons in that area (91). Eberwine and Bartfai (94) and Bartfai et al (95) have reported that a single warm-sensitive neuron in the hypothalamus may contain several hundred receptor transcripts, however.…”
Section: Discussionmentioning
confidence: 99%
“…Several glutamatergic cell groups are present in the vPAG (90-93, 140, 141), including VGLUT3 projection neurons in the midline area, many of which represent 5-HT neurons, clearly separated from the GABA (GAD67) neurons (91). The VGLUT3 + neurons are likely not GALR1 + in view of their mainly midline localization.…”
Section: Discussionmentioning
confidence: 99%
“…McDavitt et al, (2014) also showed that stimulation of this DR to VM pathway generates glutamatergic excitatory postsynaptic current in VM dopamine neurons, and that the rewarding effect associated with its activation is blocked by a selective dopamine D1 antagonist. A substantial number of DR neurons express VGluT3, which constitutes a major part of the DR efferent projection to the ventral midbrain (Hioki et al, 2010;Qi et al, 2014;Watabe-Uchida et al, 2012). Dorsal raphe glutamatergic neurons also establish asymetrical synaptic connections with VM dopamine neurons (Qi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance of the patch pipette was 3-6 M⍀ when filled with the standard intracellular solution containing the following (in mM): 6 KCl, 130 K D-gluconate, 10 NaCl, 10 HEPES, 0.5 EGTA, 0.1 CaCl 2 , 2 MgCl 2 , 4 Na-ATP, and 0.4 Na-GTP, pH 7.3, adjusted with KOH. The lateral wing subdivision of the DRN (DRL) was selected as the recording region because the density of GAD67-positive 5-HT neurons was relatively higher than in ventral or dorsal parts of the DRN (Hioki et al, 2010). After whole-cell recording from DR neurons held at a membrane potential of Ϫ70 mV and switched to current-clamp recording mode, membrane potentials were recorded with an Axopatch 200B amplifier (Molecular Devices) and obtained by stepwise current injections (from Ϫ0.2 to 0.5 nA; duration, 500 ms).…”
Section: Methodsmentioning
confidence: 99%
“…Of these, GABAergic and 5-HTergic transmissions can negatively regulate 5-HT release (Gallager and Aghajanian, 1976;Piñeyro and Blier, 1999), and are thereby considered possible targets of therapeutic interventions. Interestingly, some 5-HTergic neurons have been shown to express GABA or its synthetic enzyme glutamic acid decarboxylase (GAD) (Nanopoulos et al, 1982;Belin et al, 1983;Fu et al, 2010;Hioki et al, 2010), suggesting a possible corelease of 5-HT and GABA. In this regard, these neurons may have a unique mechanism that controls their firing activity through autoregulatory feedback inhibition.…”
Section: Introductionmentioning
confidence: 99%